PENGARUH BEBAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT TIKI JALUR NUGRAHA EKAKURIR (JNE EXPRESS) CABANG BANDARA MAS KOTA TANGERANG - Trinandita Rahma Ayuningtyas; Theobaldus Boro Tura (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the effect of Workload and Job Satisfaction on Employee Performance at PT Tiki Jalur Nugraha Ekakurir (JNE Express) Bandara Mas Branch, Tangerang City, both partially and simultaneously. The research method used in this study is a quantitative method. The sample consisted of 75 employees. Data collection techniques were conducted through primary data and secondary data. Data analysis techniques included validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-test, and F-test. The results of the study indicate that: (1) partially, workload has a positive and significant effect on employee performance, as evidenced by the regression equation Y = 23.201 + 0.485X₁, with a t-value of 5.732 greater than the t-table value of 1.992 and a significance value of 0.000 < 0.05. (2) Partially, job satisfaction has a positive and significant effect on employee performance, as indicated by the regression equation Y = 19.927 + 0.560X₂, with a t-value of 7.758 greater than the t-table value of 1.992 and a significance value of 0.000 < 0.05. (3) Simultaneously, workload and job satisfaction have a positive and significant effect on employee performance, as evidenced by the multiple linear regression equation Y = 15.229 + 0.236X₁ + 0.437X₂, a correlation coefficient of 0.710, a coefficient of determination of 50.4%, and an F-value of 6.509 greater than the F-table value of 3.12, with a significance value of 0.000 < 0.05.